Pengembangan Augmented Reality Sebagai Electronic Performance Support System dalam Pembelajaran - Yerry Soepriyanto; Sulthoni; Saida Ulfa (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2017)
Students sometimes find it difficult to illustrate learning content in the form of knowledge of concepts and procedures. Therefore, this development aims to produce a product in the form of Augmented Reality that is valid for use in learning performance support electronic systems (Electronic Performance Support System). Markers are placed on teaching materials on the part of the image that illustrates a concept, so that when students do not fully understand, the smartphone camera used as a marker detector captures and runs the media to convey knowledge in the form of video and animation. This study uses the Lee-Owen development model with three stages of completion. The result of the development is an Augmented Reality application which is used as a support system for learning performance in teaching materials in valid categories.